GENETIC DIVERSITY BASED ON CLUSTER AND PRINCIPAL COMPONENT ANALYSIS FOR YIELD, YIELD COMPONENTS AND QUALITY TRAITS IN PEANUT STEM NECROSIS TOLERANT GROUNDNUT (Arachis hypogaea L.) GENOTYPES - P. DHARANI NIVEDITHA; M. SUDHARANI; P.J. NIRMALA (The Journal of Research ANGRAU, 2016)
The present research work was carried out to excavate diverse parents and to determine selection parameters for Peanut Stem Necrosis tolerance in groundnut. It was carried out to estimate genetic diversity by principal component analysis(PCA) for fifteen yield, yield components and quality traits in fifty groundnut genotypes at Agricultural Research Station, Kadiri during kharif, 2015. First five principal components (PC1, PC2, PC3, PC4 and PC5) have Eigen values greater than one and accounted for 71.46 per cent of total variability and account with values of 23.39%, 18.20%, 12.22%, 10.01% and 7.64%, respectively. PC1 has positive association with haulm yield plant-1, shelling per cent, kernel yield, number of filled pods plant-1, oil content, SCMR at 60 DAS, pod yield plant-1, total pods plant-1, days to 50 per cent flowering and protein content. PC2 is positively associated with harvest index, days to 50 per cent flowering, shelling per cent and plant height.